2016
DOI: 10.1039/c6ob00557h
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselectivity and stereoselectivity of cyclisation pathways leading to bicyclic tetramates controlled by ring-chain tautomerisation in thiazolidines

Abstract: Chemoselective Dieckmann cyclisation reactions on N-malonyl thiazolidine templates derived from cysteine and pivaldehyde or aromatic aldehydes may be used to access bicyclic tetramates, for which different pathways operate as a result of differing ring-chain tautomeric behaviour of the respective intermediate imines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…Broth assays were performed to determine MICs of compounds (Table 10, 9b-f, h, l-m, q, u-v, z showed an MIC of 0.49 µg/mL against at least one organism, significantly better than the tetramate ester analogues 8a-g, 12 highlighting the importance of a carboxamide side chain group for whole-cell antibacterial activity. However, the presence of more polar carboxamides at C-7 led to a loss of activity (see 9d' and 9e').…”
Section: Broth Dilution Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Broth assays were performed to determine MICs of compounds (Table 10, 9b-f, h, l-m, q, u-v, z showed an MIC of 0.49 µg/mL against at least one organism, significantly better than the tetramate ester analogues 8a-g, 12 highlighting the importance of a carboxamide side chain group for whole-cell antibacterial activity. However, the presence of more polar carboxamides at C-7 led to a loss of activity (see 9d' and 9e').…”
Section: Broth Dilution Methodsmentioning
confidence: 99%
“…General procedure: Synthesis of N-acylated thiazolidines 6,7. 12 Step 1: To ʟ-cysteine methyl ester hydrochloride (1.0 eq) in petrol (25 mL/1 g), Et 3 N (1.2 eq) and aldehyde (1.2 eq) were added. The mixture was heated at reflux, with continuous removal of water using a Dean-Stark apparatus, for 19 h. It was then filtered and washed with Et 2 O.…”
Section: Broth Dilution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ing that thiazolidines would be more stable, we reacted cysteine and a range of aldehydes, and found them this time to be stable but to favour the trans-diastereomers 64a'-g' rather than the expected cis-diastereomers 64a-g. 77,108 Cyclisation of 64a'-g' gave not the expected product from Route a (Scheme 7), but the alternative Route b (Scheme 7) leading to 65a-g (Scheme 8), so that the entire reaction sequence was found not to be exactly comparable to the oxazolidines described above (Scheme 7); we believe that this is due principally to the reduced bulk of the aryl residue relative to the tert-butyl group. Of interest was the observation of strong scalar cross relaxation in the NMR spectra of the thiazolidine systems.…”
Section: Short Review Syn Thesismentioning
confidence: 91%
“…It has previously been shown that the tetramate 16 derived from cysteine may be prepared with aromatic groups at the C(3) position, and that in this case tetramate cyclisation leads to isomer 16. 50 To obtain the C(6)-unsubstituted analogue suitable for spirocyclisation, ethyl ester 16 was refluxed to yield decarboxylated 17. However, treatment with aldehyde 6b resulted again in recovered starting material.…”
Section: Methodsmentioning
confidence: 99%